UNCOVERING THE SECRETS OF FINANCIAL SECTOR COMPANY VALUES: A STUDY OF THE INFLUENCE OF INSTITUTIONAL OWNERSHIP, OPERATING CASH FLOW, AND LEVERAGE ON THE INDONESIA STOCK EXCHANGE (2020-2024) - Yusuf Faisal; Nicholla Anggelita Adinda Elta (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2026)
This study aims to obtain empirical evidence on the effect of institutional ownership, operating cash flow, and leverage on firm value. This study uses quantitative research. The sample in this study consists of 70 financial sector companies listed on the Indonesia Stock Exchange in 2020-2024. The analysis technique used to test the hypothesis is multiple regression analysis using Eviews 9 software. The results of this study found that institutional ownership has a negative effect and is statistically insignificant on firm value, while operating cash flow has a negative effect and is statistically significant on firm value. Meanwhile, leverage has a negative effect and is statistically insignificant on firm value. This study discusses firm value and other factors such as institutional ownership, operating cash flow, and leverage, focusing on the financial sector.